2014
DOI: 10.1159/000365038
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Bone Mass in 7-Year-Old Children with Asymptomatic Idiopathic Hypercalciuria

Abstract: Background: Idiopathic hypercalciuria (IHC), i.e. an elevated urinary calcium excretion without concomitant hypercalcemia, is a common disorder in children and can have a range of urinary clinical presentations and decreased bone mineral density (BMD). Aim: To assess the effect of IHC on bone mineral content in children without urological symptoms. Methods: Calcium excretion, BMD (by dual-energy X-ray absorptiometry), and anthropometry were assessed in 175 seven-year-old children who were classified as IHC or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Balestracci et al have reported the prevalence of 20% for idiopathic hypercalciuria among children with urinary tract infection (12). Also, the association of idiopathic hypercalciuria and reduced bone mineral density is suggested by some researchers (13, 14). It is shown that dietary interventions may reduce the complications of idiopathic hypercalciuria (15).…”
Section: Introductionmentioning
confidence: 95%
“…Balestracci et al have reported the prevalence of 20% for idiopathic hypercalciuria among children with urinary tract infection (12). Also, the association of idiopathic hypercalciuria and reduced bone mineral density is suggested by some researchers (13, 14). It is shown that dietary interventions may reduce the complications of idiopathic hypercalciuria (15).…”
Section: Introductionmentioning
confidence: 95%
“…Long-term increased urinary calcium excretion may affect health outcomes, such as bone mass accretion [1] and urolithiasis risk [2,3]. Normal ranges of calciuria have been widely studied in adults and children [4,5,6], but few data exist in infants younger than 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Different study designs have been found: descriptive cross sectional studies [6, 11-19, 23-25, 28, 30-33, 36-38, 40, 41], cross sectional studies with control group [21,22,34,44], case-control studies [10,20,29,43], randomized controlled trial [27,35,39], cohort studies [9,26,45,46], one prospective study [42], and four PhD Studies [47][48][49][50].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Concerning the first concept, 5 FFQ were quantitative [34,44] or semi-quantitative [22,35,40] ranging from 54 to 140 items. The time-specific period varies by being annual [29,43] or monthly [20,21].…”
Section: Calcium Intake Assessmentmentioning
confidence: 99%
See 1 more Smart Citation